1976
DOI: 10.1098/rspa.1976.0173
|View full text |Cite
|
Sign up to set email alerts
|

Laminar natural convection boundary layers on near-horizontal plates

Abstract: The first order boundary-layer analysis for the laminar natural convection flow over a semi-infinite horizontal or near-horizontal heated plate has been extended to include variable properties effects. Detailed calculations are presented for air and water flows. It is shown further how these calculations can be extended to predict heat transfer rates on plates of rectangular planforms. Because of the lack of sufficiently detailed experimental data, a thorough comparison between the latter and the present calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…In relation to analytical and/or numerical studies of the natural convective heat transfer phenomena in flat surfaces, there are the works of Ackroyd (1976), Bandrowski and Rybski (1976), Goldstein and Lau (1983), Chen et al (1986) and Wei et al (2003) as fundamental references.…”
Section: Parameters In Turbulent Simulationsmentioning
confidence: 99%
“…In relation to analytical and/or numerical studies of the natural convective heat transfer phenomena in flat surfaces, there are the works of Ackroyd (1976), Bandrowski and Rybski (1976), Goldstein and Lau (1983), Chen et al (1986) and Wei et al (2003) as fundamental references.…”
Section: Parameters In Turbulent Simulationsmentioning
confidence: 99%
“…As classic references and basic theoretical rationale on the analytical and numerical study of natural convection in rectangular flat plates, the works of Ackroyd (1976), Bandrowski and Rybski (1976), Goldstein and Lau (1983), Chen et al (1986) and Wei et al (2003).…”
Section: Introductionmentioning
confidence: 99%
“…While they observed flow partitioning through collision lines for the boundary layer along the plate edges for each of the planforms, in the case of the circular plate, they found radially accelerating flow from the edges, which then transitioned into a billowing plume at the center. Ackroyd [7] investigated the edge flows and fluid property variations for rectangular horizontal plates and Al-Arabi and El-Riedy [8] conducted further heat transfer studies on plates of various shapes, and observed both edge and corner effects, whereas Garcia-Ybarra and Trevino [9] analyzed the thermal diffusion effects of hydrogen-air mixtures within the development of a boundary layer on a hot flat plate. Heat transfer experimental studies have also been performed circular cylindrical conduit [12], on finned tubes to determine the effect on refrigeration efficiency [13], and basic analysis on a heated cylinder [18].…”
Section: Figure 1 Hot Surface Flow Mechanismmentioning
confidence: 99%